Microwave-assisted One-Pot Synthesis of 2-Aryl (1H) Benzimidazoles without Catalyst - Jassim Mohammed Abdullah; Mohammed Mahmood Sulaiman; Salim J. Mohammed (مجلة التربية والعلم, 2012)
ABSTRACT We described a simple, fast and efficient procedure for solvent free Microwave-assisted one pot synthesis of a series of 2-aryl-H-bezimidazoles by condensation of o-Phenylenediamine with suitable aromatic aldehyde. The structures of the products were confirmed by physical and spectral data.